Z세대가 즐기는 유튜브 채널의 몰입 요인과 특징 - 강민정(MinJeong Kang); 정은주(Eun-Ju Jeong); 조해윤(Hae-Yoon Cho) (한국콘텐츠학회 논문지, 20(2), 2020)
Generation Z(Gen Z), which is referred to people in their late teens to early 20s, becomes one of new major consumer groups in the society. More than 80 percent Gen Z use YouTube content as a main information channel. In this study, we investigate what kind of factors make Gen Z immersed when watching YouTube content. In the background study, we examined immersion and set the cognitive conditions of immersion as reality, fascination, control, and driving as a framework for analysis of case study. In the case study, we analyzed the most popular YouTube channels of each category among the Gen Z with the established framework and then identified 3 main factors: reality, 5 senses, and unpretentiousness and 8 characteristics of them. By conducting survey with Gen Z, we wanted to verify the validity of the characteristics and find out the difference among categories. Subjects answered on a five-point scale how the characteristics of each immersion factor corresponded to their favorite channels. As a result, seven characteristics: 1) familiarity of background, 2) reality of acting, 3)familiarity of material, 4)YouTubers' appearance and 5) voice, 6)multi-sensory, and 7)YouTuber's ability to resemble viewers influenced more than 50% of users' immersion. Although there was no significant difference among categories, the familiarity of the material and the five senses stimulus (YouTube's appearance, voice, audiovisual and surrogate taste) were the most important factors in the entertainment category. 소비의 주축으로 주목받고 있는 Z세대는 10대 후반에서 20대 초반의 연령대로서 80% 이상이 유튜브 콘텐츠를 이용하고 있다. 본 연구는 Z세대가 유튜브 콘텐츠에서 어떻게 몰입을 느끼는지 그 요인을 알아내고자 하였다. 배경연구에서 몰입에 대해 고찰을 하고 몰입의 인지조건인 현실감, 매혹감, 제어감, 추동감을 분석 프레임으로 설정하였다. 사례연구에서는 분석 프레임을 통해 Z세대들이 가장 많이 즐기는 유튜브 채널들을 카테고리별로 분석하여 몰입의 3가지 주요 요인, 현실감, 오감자극, 솔직함을 밝혀내었다. 각 요인별 특징들을 8가지로 세분화하여 유효성을 검증하고 카테고리별 차이점을 밝히고자 Z세대들을 대상으로 설문조사를 하였다. 피험자들은 각 몰입요인의 특징이 자신이 가장 즐겨보는 채널을 기준으로 어느 정도 해당하는지를 5점 척도로 답하였고 결과로서 총 7가지 특징, 배경의 친숙함, 진행의 리얼리티, 소재의 친숙함, 유투버의 외모, 목소리, 시청각/대리미각, 시청자와 비슷한 유투버의 능력에 대해서 사용자의 50% 이상 몰입에 영향을 준다고 답하였다. 카테고리별 차이는 크게 나타나지 않았지만 엔터테인먼트 카테고리에서는 소재의 친숙성과 오감자극(유투버의 외모, 목소리, 시청각/대리미각)이 두드러지게 중요한 요인으로 나타났다. 이 연구 결과는 Z세대를 대상으로 한 영상 콘텐츠를 생산하는데 중요한 기준이 될 것이라 기대한다.